2018
DOI: 10.1186/s13741-018-0098-3
|View full text |Cite|
|
Sign up to set email alerts
|

Intraoperative oxygenation in adult patients undergoing surgery (iOPS): a retrospective observational study across 29 UK hospitals

Abstract: BackgroundConsiderable controversy remains about how much oxygen patients should receive during surgery. The 2016 World Health Organization (WHO) guidelines recommend that intubated patients receive a fractional inspired oxygen concentration (FIO2) of 0.8 throughout abdominal surgery to reduce the risk of surgical site infection. However, this recommendation has been widely criticised by anaesthetists and evidence from other clinical contexts has suggested that giving a high concentration of oxygen might worse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 23 publications
1
23
1
Order By: Relevance
“…Furthermore, this variability is linked to clinical outcomes . Similar patterns of variation in care pertain in peri‐operative blood transfusion , oxygen therapy and peri‐operative ventilation . These observations support the notion that intra‐operative care should be both standardised and individualised; standardised to drive consistent patterns of care between different patients, and individualised to ensure that such care is based on individual patients’ clinical risk.…”
Section: Peri‐operative Care Pathwayssupporting
confidence: 57%
“…Furthermore, this variability is linked to clinical outcomes . Similar patterns of variation in care pertain in peri‐operative blood transfusion , oxygen therapy and peri‐operative ventilation . These observations support the notion that intra‐operative care should be both standardised and individualised; standardised to drive consistent patterns of care between different patients, and individualised to ensure that such care is based on individual patients’ clinical risk.…”
Section: Peri‐operative Care Pathwayssupporting
confidence: 57%
“…Moreover, while routine supplemental oxygen administration is not recommended for non-hypoxemic patients with several acute conditions, such as acute coronary syndrome [ 1 , 2 ] and stroke [ 3 , 4 ], the postoperative period is one of the few circumstances where high-dose oxygen therapy has been recommended to reduce surgical site infections (SSIs) [ 5 ]. However, such recommendations remain controversial and have not been widely accepted in actual clinical practice [ 6 8 ]. The present paper therefore reviews the rationale, clinical significance, and controversies regarding postoperative oxygen therapy and re-evaluates the optimal use of postoperative oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…In brief, the reference patients had undergone recent induction of anesthesia with intravenous opiates (usually fentanyl) and propofol, muscle relaxation using atracurium or rocuronium, and placement of an endotracheal tube for mechanical ventilation and maintenance of anesthesia with volatile agents such as isoflurane, sevoflurane or desflurane. An audit carried out at the Royal Free Hospital, along with 28 other hospitals in England, during the time of the study, demonstrated the administration of a consistent fractional concentration of oxygen of 0.5 throughout surgery, which corresponded to a measured mean partial pressure of oxygen (PaO2) of 25 kPa in patients with an arterial catheter [ 61 ]. All elective surgical patients had fasted for at least 6 h prior to induction of general anesthetic.…”
Section: Methodsmentioning
confidence: 99%